2019
DOI: 10.1108/er-11-2017-0285
|View full text |Cite
|
Sign up to set email alerts
|

Just benefits? Employee benefits and organisational justice

Abstract: Purpose Employee reward is central to contemporary debates about work and employment relations; and in the context of ongoing wage stagnation, benefits represent a growing proportion of total reward value. Past studies have shown that when employees perceive benefits as unfair, this has a negative impact on engagement, performance and retention. Yet no previous studies have explored the components of a benefits system that influence employees’ fairness concerns. Using organisational justice as a theoretical le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
2
12
0
2
Order By: Relevance
“…These findings also suggest that perceived inequity in terms of pay and career progression can lead to lower levels of motivation and increased levels of employee turnover, which could have a negative impact on the organisation through the loss of knowledge. These findings echo the broader organisational justice literature, which has identified that perceived reward and procedural fairness in organisations is associated with broader organisational outcomes such as performance and job satisfaction (Cohen-Charash and Spector, 2001; Laundon et al , 2019; Greenberg and Colquitt, 2013).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These findings also suggest that perceived inequity in terms of pay and career progression can lead to lower levels of motivation and increased levels of employee turnover, which could have a negative impact on the organisation through the loss of knowledge. These findings echo the broader organisational justice literature, which has identified that perceived reward and procedural fairness in organisations is associated with broader organisational outcomes such as performance and job satisfaction (Cohen-Charash and Spector, 2001; Laundon et al , 2019; Greenberg and Colquitt, 2013).…”
Section: Resultssupporting
confidence: 78%
“…High turnover and demotivated staff are associated with poor organisational outcomes (Alcoba and Phinaitrup, 2020; Stritch et al , 2018; Fernet et al , 2015; Bellé, 2013). These findings further resonate with the literature on organisational justice (Laundon et al , 2019; Cohen-Charash and Spector, 2001), and there is scope for further research to be undertaken from an organisational justice perspective in the FRS that could develop fruitful recommendations for management practices in the PRS. In the meantime, based on the findings of this paper and the broader literature, the FRS may find it worthwhile to remove the barriers community safety employees face in their organisations, especially as these roles are becoming a new “front line” for the FRS and responding to complex and vulnerable cases.…”
Section: Discussionsupporting
confidence: 73%
“…"Visión de Futuro" Año 17, Volumen Nº 24 Nº 2, Julio -Diciembre 2020 -Pág 166 -183 URL de la Revista: http://visiondefuturo.fce.unam.edu.ar/index.php/visiondefuturo/index URL del Documento: https://visiondefuturo.fce.unam.edu.ar/index.php/visiondefuturo/issue/view/18 ISSN 1668 -8708 -Versión en Línea E-mail: revistacientifica@fce.unam.edu.ar Organizacionalmente, las recompensas tienen dos objetivos principales: motivar el desempeño individual y mantener la cohesión del grupo (Cropanzano et al, 2007), es por esto que los empleados de alto desempeño o aquellos con habilidades poco frecuentes de encontrar en el mercado, a la luz de la equidad, deberían tener mayores salarios y otro tipo de incentivos (Laundon, Cathcart, & McDonald, 2019). En este punto, la justicia interaccional cobra una gran importancia, puesto que es a través de un proceso comunicativo en donde quedan explícitas las diferencias salariales y de otro tipo de recompensas que se otorgan en el ámbito organizacional, pudiendo así establecer que la justicia de la información tiene un papel mediador entre algunas recompensas y la satisfacción laboral (Gangloff, Mayoral, Personnaz, & Rezazi, 2016;Long, 2016).…”
Section: Distribución De Las Recompensasunclassified
“…Organizacionalmente, las recompensas tienen dos objetivos principales: motivar el desempeño individual y mantener la cohesión del grupo (Cropanzano et al, 2007), es por esto que los empleados de alto desempeño o aquellos con habilidades poco frecuentes de encontrar en el mercado, a la luz de la equidad, deberían tener mayores salarios y otro tipo de incentivos (Laundon, Cathcart, & McDonald, 2019). En este punto, la justicia interaccional cobra una gran importancia, puesto que es a través de un proceso comunicativo en donde quedan explícitas las diferencias salariales y de otro tipo de recompensas que se otorgan en el ámbito organizacional, pudiendo así establecer que la justicia de la información tiene un papel mediador entre algunas recompensas y la satisfacción laboral (Gangloff, Mayoral, Personnaz, & Rezazi, 2016;Long, 2016).…”
Section: Distribución De Las Recompensasunclassified